Nosological profile and prevalence of common mental disorders of patients seen at the Family Health Program (FHP) units in Petrópolis, Rio de Janeiro - Fortes,Sandra (2008)
OBJECTIVES: This study aims to detect the prevalence of common mental disorders among patients seen by doctors at family health program units in Petrópolis-RJ, and to establish their nosological profile. METHOD: The population of the study included all 18 to 65-year-old patient who attended any family health program units included in the study during a 30-day period, between August and December 2002 (n = 714). The prevalence of common mental disorders was assessed using the General Health Questionnaire, 12 item version. In order to establish the nosological profile, the Composite International Diagnostic Interview was administered to all common mental disorders positive patients who accepted to return (n = 215). RESULTS: At the cut-off point of 2/3 the common mental disorders prevalence was 56% and for 4/5, it was 33%. The most frequent nosological categories found among common mental disorders positive patients were depression and anxiety categories along with posttraumatic stress disorder, somatoform pain disorder and dissociative disorders. There was a high frequency of comorbidity, especially between anxiety, depression, somatoform and dissociative disorders. CONCLUSIONS: The common mental disorders prevalence and the nosological profile found in FHP were similar to those of other primary care studies in Brazil, but some disorders (posttraumatic stress disorder, somatoform pain disorder and dissociative disorders) that had not been previously studied in this context were also very frequent. The high common mental disorders prevalence found reinforces the urgent need for systematic inclusion of this level of care in mental health assistance planning.